Eksplorasi Penggunaan AI Generatif untuk Menciptakan Materi Pembelajaran Bahasa Indonesia yang Menarik dan Efektif - Shohifur Rizal, Moh. Ahsan (Innovative: Journal Of Social Science Research, 2024)
Artificial Intelligence (AI) has great potential to revolutionize Indonesian language learning. AI can be used to create more personalized, engaging, and effective learning experiences. Indonesian is the language of unity and the national language of Indonesia. It is important for every Indonesian citizen to master the Indonesian language well. Creative and engaging Indonesian language learning can help students achieve their goals. This research uses a qualitative method with a library study design. This research uses a library study method to explore the potential of generative AI in creating creative and engaging Indonesian language learning materials. Data is collected from various trusted sources, such as scientific journals, research articles, books, and official reports. Generative artificial intelligence (generative AI) is a branch of AI that is capable of generating new content, such as text, images, and audio. Generative AI has great potential to improve the quality and accessibility of education. Generative AI has several advantages over traditional methods in generating learning materials. Generative AI can generate personalized content based on individual student needs. This research explores the use of generative AI to create creative and engaging Indonesian language learning materials. This research finds that generative AI can be used to generate various types of Indonesian language learning materials, such as story texts, poems, dialogues, and practice problems. Learning materials generated by generative AI have been shown to increase student motivation and learning outcomes.